2003
DOI: 10.1002/jclp.10187
|View full text |Cite
|
Sign up to set email alerts
|

The Schizophrenia Proneness (SzP) scale: An MMPI‐2 measure of schizophrenia liability

Abstract: We examined the psychometric properties and construct validity for a Minnesota Multiphasic Personality Inventory-2 Schizophrenia Proneness (SzP) scale (Bolinskey et al., 2001) and provided normative statistics. Premorbid participants were offspring of parents with schizophrenia-related illness (SRI), with comparison groups of offspring of parents with major affective disorders and offspring of normals. Postmorbid participants were twins affected with SRI; their unaffected relatives served as a comparison group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…Results from much of this research has indicated that these disorders are best represented as multidimensional constructs, and recent efforts have been aimed at empirically deriving clusters of symptomatology in each disorder within a variety of clinical and non-clinical samples. Of the three Cluster A disorders, SPD is the most common, and the bulk of this research has focused on the measurement of “schizotypal” signs or symptoms using self-report inventories that have been developed to measure a multidimensional “schizotypy” construct (Bolinsky et al 2003; Claridge and Broks 1984; Nielsen and Petersen 1976; Rust 1987; 1988; Mason et al 1995; Venables et al 1990). …”
Section: Measurement Of Cluster a Personality Disordersmentioning
confidence: 99%
“…Results from much of this research has indicated that these disorders are best represented as multidimensional constructs, and recent efforts have been aimed at empirically deriving clusters of symptomatology in each disorder within a variety of clinical and non-clinical samples. Of the three Cluster A disorders, SPD is the most common, and the bulk of this research has focused on the measurement of “schizotypal” signs or symptoms using self-report inventories that have been developed to measure a multidimensional “schizotypy” construct (Bolinsky et al 2003; Claridge and Broks 1984; Nielsen and Petersen 1976; Rust 1987; 1988; Mason et al 1995; Venables et al 1990). …”
Section: Measurement Of Cluster a Personality Disordersmentioning
confidence: 99%
“…The Moldin-Gottesman index of MMPI-based signs of schizophrenia both differentiated the high-risk offspring from affective disorder and also from non-psychiatric controls (Moldin et al, 1990). This index also predicted the later onset of schizophrenia-related psychosis (SRP) with 82.1% accuracy, and another set of MMPI indicators predicted SRP in adulthood with 95.1% accuracy, among subjects in all three groups who were followed into adulthood (Bolinskey et al, 2001(Bolinskey et al, , 2003. In a 25-year follow-up study of a large Danish sample of high-risk offspring tested with the MMPI during adolescence, the later development of schizophrenia was predicted by shortened forms of MMPI scales F, PHO (Phobias), and the summed index of scales D, Pt, Sc, and Si (Social introversion), with 14% of the variance in prediction accounted for by these MMPI indicators (Carter et al, 1999).…”
Section: Introductionmentioning
confidence: 97%
“…Several following studies (e.g., Bolinskey, Gottesman, Nichols et al , 2001; Bolinskey, Gottesman & Nichols, 2003; Carter, Parnas, Cannon, Schulsinger & Mednick, 1999) have incorporated prospective designs to determine MMPI‐determined personality characteristics predictive of future schizophrenia. Bolinskey et al (2001) incorporated a prospective, high‐risk paradigm to re‐examine the predictive power of the indicators in the Moldin index using SADS‐derived (Spitzer & Endicott, 1978) Axis I diagnoses as the basis for criterion group membership.…”
Section: Introductionmentioning
confidence: 99%
“…Bolinskey et al (2001) incorporated a prospective, high‐risk paradigm to re‐examine the predictive power of the indicators in the Moldin index using SADS‐derived (Spitzer & Endicott, 1978) Axis I diagnoses as the basis for criterion group membership. Results suggested that eight MMPI scales ( L , Lie Scale; K , Defensiveness/Correction Scale; 2780 , a linear combination of the Depression, Psychasthenia, Schizophrenia, and Social Introversion scales, respectively (Golden & Meehl, 1979); SOC , PSY , PHO , Wiggins’ (1966) Social Maladjustment, Psychoticism, and Phobias Content Scales; Gilberstadt and Gottesman's 8‐6 scale (Minnesota Veterans Administration Hospital, 1975), and SzP , Schizophrenia Proneness (Bolinskey et al , 2003)) were the most effective indicators of future onset of schizophrenia‐related psychosis. Likewise, Carter et al (1999) found evidence for the power of five scales in the Moldin index ( F , Infrequency Scale; L , 2780 , Pz , Rosen's (1962) Paranoid Schizophrenia Scale; and PHO ) to separate individuals who later developed schizophrenia from those who developed no psychopathology.…”
Section: Introductionmentioning
confidence: 99%